PML, YAP, and p73 are components of a proapoptotic autoregulatory feedback loop. - Lapi, E; Di Agostino, S; Donzelli, S; Gal, H; Domany, E; Rechavi, G; Pandolfi, P; Givol, D; Strano, S; Lu, X; Blandino, G (2008)
p73 has been identified as a structural and functional homolog of the tumor suppressor p53. The transcriptional coactivator Yes-associated protein (YAP) has been demonstrated to interact with and to enhance p73-dependent apoptosis in response to DNA damage. Here, we show the existence of a proapoptotic autoregulatory feedback loop between p73, YAP, and the promyelocytic leukemia (PML) tumor suppressor gene. We demonstrate that PML is a direct transcriptional target of p73/YAP, and we show that PML transcriptional activation by p73/YAP is under the negative control of the proto-oncogenic Akt/PKB kinase. Importantly, we find that PML and YAP physically interact through their PVPVY and WW domains, respectively, causing PML-mediated sumoylation and stabilization of YAP. Hence, we determine a mechanistic pathway in response to DNA damage that could have relevant implications for the treatment of human cancer.